The Reduction of Blood Pressure in Mrs. R’s Family Following Finger Grip Relaxation and Progressive Muscle Relaxation Therapy - Alfian, Alfian; Sutria, Eny; Rasdiyanah, Rasdiyanah; Rasmawati, Rasmawati; Fitriani, Aidah (PABBURA : Health Service Journal, 2024)
The prevalence of hypertension has been increasing from year to year. Findings from the Basic Health Research (Riskesdas) indicate that the percentage of hypertension patients was 25% in 2013, which increased to 34.1% in 2018. Psychosocial anxiety or stress is one of the factors influencing blood pressure elevation. One method of stress management is through the utilization of finger grip relaxation and progressive muscle relaxation techniques. The aim of community service is to apply nursing care with interventions of finger grip relaxation and muscle relaxation to families experiencing hypertension. The method employed involves assisting families with hypertension issues through the implementation of nursing interventions such as finger grip relaxation therapy for three days and progressive muscle relaxation for two days, alongside health education regarding hypertension. The results demonstrate a reduction in blood pressure evaluated daily during and after therapy administration, as well as an enhancement in the ability of Mrs. R’s family to independently perform therapy. The application of finger grip relaxation and progressive muscle relaxation therapy can be routinely implemented for clients experiencing hypertension.